2016
DOI: 10.1016/j.frl.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin, gold and the dollar – A GARCH volatility analysis

Abstract: This paper explores the financial asset capabilities of bitcoin using GARCH models. The initial model showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange. The asymmetric GARCH showed that bitcoin may be useful in risk management and ideal for risk averse investors in anticipation of negative shocks to the market. Overall bitcoin has a place on the financial markets and in portfolio management as it can be classified as something in between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
728
4
35

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,284 publications
(814 citation statements)
references
References 5 publications
47
728
4
35
Order By: Relevance
“…Accordingly, the volatility of Bitcoin decreases less as the price of Bitcoin increases, leading to an inverted asymmetry phenomenon. This interesting finding concurs with that reported for gold (Baur, 2012), and adds further evidence to the similarities between gold and Bitcoin (Dyhrberg, 2015b). Another plausible explanation of the findings relates to investors' quest for a safe-haven asset in an environment of weak trust, such as during the global financial crisis (GFC) and post-GFC periods, in particular during the ESDC.…”
Section: Table 2 Coefficient Estimates Of the Asymmetric-garch Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…Accordingly, the volatility of Bitcoin decreases less as the price of Bitcoin increases, leading to an inverted asymmetry phenomenon. This interesting finding concurs with that reported for gold (Baur, 2012), and adds further evidence to the similarities between gold and Bitcoin (Dyhrberg, 2015b). Another plausible explanation of the findings relates to investors' quest for a safe-haven asset in an environment of weak trust, such as during the global financial crisis (GFC) and post-GFC periods, in particular during the ESDC.…”
Section: Table 2 Coefficient Estimates Of the Asymmetric-garch Modelsupporting
confidence: 87%
“…Bouri et al (2016) examine the volatility persistence in the Bitcoin market. However, Dyhrberg (2015a) highlights the hedging ability of Bitcoin against the USD/EUR and USD/GBP exchange rates and UK equities, whereas Dyhrberg (2015b) situates the hedging capability of Bitcoin somewhere between gold and the US dollar.…”
Section: Introductionmentioning
confidence: 99%
“…Dyhrberg (2016a) investigated the hedging capabilities of Bitcoin by applying the asymmetric GARCH methodology and showed that Bitcoin can clearly be used as a hedge against stocks in the Financial Times Stock Exchange Index and against the American dollar in the shortterm. Dyhrberg (2016b) explored the financial asset capabilities of Bitcoin using GARCH models and showed several similarities to gold and the dollar indicating hedging capabilities and advantages as a medium of exchange. Katsiampa (2017) explored the optimal conditional heteroscedasticity model with regards to goodness-of-fit to Bitcoin price data, and found that the best model is the AR-CGARCH model, indicating significance of including both a short-run and a long-run component of the conditional variance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was shown that Bitcoin can be used as a hedge against stocks in the Financial Times Stock Exchange Index and against the American dollar in the short term. Dyhrberg (2016b) used GARCH models to explore the financial asset capabilities of Bitcoin. It was shown that Bitcoin has a place on the financial markets and in portfolio management as it can be classified as something in between gold and the American dollar, on a scale from pure medium of exchange advantages to pure store of value advantages.…”
Section: Introductionmentioning
confidence: 99%